10th Problem 2016

Algebra Level 1

What is the quadratic formula for the equation a x 2 + b x + c = 0 ax^2 + bx + c = 0 ?

Check out the set: 2016 Problems

x = b ± b 2 4 a c a x\quad =\quad \frac { -b\quad \pm \quad \sqrt { { b }^{ 2\quad }-\quad 4ac } }{ a } x = b ± b 4 a c 2 a x\quad =\quad \frac { -b\quad \pm \quad \sqrt { { b }^{ \quad }-\quad 4ac } }{ 2a } x = b ± b 2 4 a c 2 a x\quad =\quad \frac { b\quad \pm \quad \sqrt { { b }^{ 2\quad }-\quad 4ac } }{ 2a } x = b ± b 2 4 a c 2 a x\quad =\quad \frac { -b\quad \pm \quad \sqrt { { b }^{ 2\quad }-\quad 4ac } }{ 2a }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ananth Jayadev
Jan 1, 2016

Proof of the Quadratic Formula:

The original equation is a x 2 + b x + c = 0 ax^2 + bx + c = 0 .

Subtract the c c on both sides so a x 2 + b x = c ax^2 + bx = -c .

Divide the a a by all terms so x 2 + ( b a ) x = c a x^2 + (\frac {b}{a})x = -\frac {c}{a} .

Take half the x x term and square it so b 2 a b 2 4 a 2 \frac {b}{2a} \rightarrow \frac {b^2}{4a^2} .

Add the squared term on both sides so x 2 + ( b a ) x + b 2 4 a 2 = c a + b 2 4 a 2 x^2 + (\frac {b}{a})x + \frac {b^2}{4a^2} = -\frac {c}{a} + \frac {b^2}{4a^2} .

Simplify the RHS so x 2 + ( b a ) x + b 2 4 a 2 = 4 a c 4 a 2 + b 2 4 a 2 x^2 + (\frac {b}{a})x + \frac {b^2}{4a^2} = -\frac {4ac}{4a^2} + \frac {b^2}{4a^2} .

Convert the LHS to square form so ( x + b 2 a ) 2 = b 2 4 a c 4 a 2 (x+\frac {b}{2a})^2 = \frac {b^2 - 4ac}{4a^2} .

Square root both sides so x + b 2 a = ± b 2 4 a c 4 a 2 = ± b 2 4 a c 2 a x+\frac { b }{ 2a } =\pm \sqrt { \frac { { b }^{ 2 }-4ac }{ 4{ a }^{ 2 } } } =\quad \frac { \pm \sqrt { { b }^{ 2 }-4ac } }{ 2a } .

Solve for x x so x = b 2 a ± b 2 4 a c 2 a = b ± b 2 4 a c 2 a x = -\frac { b }{ 2a } \pm \frac { \sqrt { { b }^{ 2 }-4ac } }{ 2a } = \frac{-b \pm \sqrt{b^2-4ac}}{2a} .

Derived using Completing the Square.. Amazing :D

Angela Fajardo - 5 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...